Ovarian follicular waves and secretion of follicle-stimulating hormone after administration of GnRH at estrus - J.R. Pursley; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1992)
An experiment was conducted to examine the effects of GnRH on the secretion of FSH, LH, estradiol, and progesterone in serum and changes in ovarian structures. Dairy cows were assigned randomly to receive either 100 Î¼g of GnRH or saline 12 hr after estrus (day 0) was detected. Blood was collected daily to assess changes in serum estradiol and progesterone and every 12 min for 8 hr on days 8 and 15 after estrus to assess concentrations of FSH and LH. Diameter and number of follicles were determined daily by real-time ultrasonography. Two patterns of follicular development were observed. The day of peak diameter of each dominant follicle (three or four per cycle) was synchronous with increases in estradiol in serum. The dominant follicle grew at a faster rate in all GnRH-treated cows. We concluded that administering GnRH at estrus increased the pulse frequency of FSH on days 8 and 15 of the cycle, altered follicular dynamics of dominant follicles of the subsequent estrous cycle, and tended to increase concentrations of progesterone in serum of cows.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; GnRH; Ovarian follicles; FSH; Estradiol; Progesterone